Relationship between anesthesia method and recurrence rate after surgical treatment of ganglion cysts - Demir, Sukru; Kazez, Muhammet; Sevimli, Reşit; Key, Sefa; Gürger, Murat; Önce, Gökhan (My University, 2020)
Aim: Recurrence is frequently reported in patients operated on with the diagnosis of ganglion cyst. In this study, it was aimed to investigate the relationship between relapse and anesthesia method in patients who underwent total surgical excision.Material and Methods: 133 patients who were operated with a preliminary diagnosis of ganglion cyst in the orthopedics and traumatology Clinic between 2015-2019 were included in the study. The demographic features of the patients, the location of the cyst and the anesthesia method applied were evaluated retrospectively.Results: Of the 120 patients operated on, 76 (63.3%) were female and 44 (36.7%) were male. General anesthesia was performed in 44 (37%), sedation anesthesia in six (5%), regional anesthesia in 42 (35%), and local anesthesia in 28 (23%). During routine follow-up, 19 (15.8%) patients showed recurrence on average 6-12 months after the operation. When anesthesia method of patients who developed recurrence after surgery was examined, it was found that local anesthesia was performed in 13 (46.4%) of 19 patients.Conclusion: It has been determined that ganglion cysts are more likely to recur with local anesthesia during surgery than other anesthesia methods. The result obtained suggests that local anesthesia causes surgical failure due to the limited working field of the surgeon, the patients feel pain when deeper tissues are reached and the lack of adequate exposure.
Keywords: Tıbbi Araştırmalar Deneysel; Anestezi; Ortopedi